2004
DOI: 10.1111/j.1439-0418.2004.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of foliar chemical compounds on the development of Spodoptera litura (Fab.) in interspecific derivatives of groundnut

Abstract: Tobacco armyworm, Spodoptera litura (Fab), a polyphagous insect, is an important pest of groundnut (Arachis hypogaea L). It is one of the insect pests which had developed resistance to insecticides. Currently there are no cultivars of groundnut which express high level of resistance to S. litura. Wild species of groundnut, which show high levels of resistance, have been identified. Arachis kempff-mercadoi is one such wild species, which is reported to be resistant to S. litura, and indicated that in wild speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 18 publications
3
67
0
1
Order By: Relevance
“…In groundnut, quercetin and its glycoside rutin were related to larval mortality of the tobacco armyworm (syn. oriental leaf worm) Spodoptera litura (Mallikarjuna et al 2004). Similarly, it has been reported that the presence of some preformed antifungal compounds, such as catechin and epicatechin, proved to be responsible for resistance against gray mold (Botrytis cinerea) in strawberries (Terry et al 2004).…”
Section: Discussionmentioning
confidence: 91%
“…In groundnut, quercetin and its glycoside rutin were related to larval mortality of the tobacco armyworm (syn. oriental leaf worm) Spodoptera litura (Mallikarjuna et al 2004). Similarly, it has been reported that the presence of some preformed antifungal compounds, such as catechin and epicatechin, proved to be responsible for resistance against gray mold (Botrytis cinerea) in strawberries (Terry et al 2004).…”
Section: Discussionmentioning
confidence: 91%
“…CGA has been described as an anti-feedant and digestibility reducer in different caterpillar species (Mallikarjuna et al 2004;Johnson and Felton 2001;Simmonds and Stevenson 2001) and sucking insects such as aphids (Miles and Oertli 1993). FQA has been implicated in the resistance of sucking herbivores such as cereal aphids (Cabrera et al 1995;Havlickova et al 1996) and cereal midges (Ding et al 2000;Abdel-Aal et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a reduced bioavailability of amino acids and a decreased digestibility of dietary proteins (Felton et al, 1989(Felton et al, , 1991. This negative effect on herbivores has primarily been shown for caterpillars in vitro (Bernays et al, 2000;Beninger et al, 2004) and in vivo (Elliger et al, 1981;Huang and Renwick, 1995;Mallikarjuna et al, 2004). In addition a harmful effect of chlorogenic acid has been shown for different leaf beetles (Fulcher et al, 1998;Ikonen, et al, 2002;Jassbi, 2003) as well as for a leafhopper (Dowd and Vega, 1996) and for aphids (Miles and Oertli, 1993).…”
Section: Discussionmentioning
confidence: 99%